2005
DOI: 10.1021/la051049r
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selective Protein Adsorption to Polystyrene Surfaces by Self-Assembled Grafted Poly(ethylene Glycols) with Varied Chain Lengths

Abstract: We report about the surface modification of polystyrene (PSt) with photoreactive alpha-4-azidobenzoyl-omega-methoxy poly(ethylene glycol)s (ABMPEG) of three different molecular weights (MWs of approximately 2, approximately 5, and approximately 10 kg/mol) and with two poly(ethylene glycol)/poly(propylene glycol) triblock copolymers (PEG-PPG-PEG) of about identical PEG/PPG ratio (80/20, w/w) and MW(PEG) of approximately 3 and approximately 6 kg/mol, all via adsorption from aqueous solutions. For ABMPEGs, an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 49 publications
2
51
0
Order By: Relevance
“…Similar observations were made with polysulphone membranes or polystyrene on which hydrophilic, non-charged poly(ethylene glycol) was covalently immobilised. [36,37] Since the quantities of polar (charged) amine functionalities were higher on PETIM_60, the lower water CAs can be explained.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were made with polysulphone membranes or polystyrene on which hydrophilic, non-charged poly(ethylene glycol) was covalently immobilised. [36,37] Since the quantities of polar (charged) amine functionalities were higher on PETIM_60, the lower water CAs can be explained.…”
Section: Discussionmentioning
confidence: 99%
“…The protein resistance of PEG modified surfaces is attributed mainly to entropic repulsion and the high water content of the PEG chains. Among other methods, PEG chains may be immobilized on surfaces via covalent coupling, either by "grafting to" [16][17][18][19] or "grafting from," 20 via the adsorption of PEG-containing block copolymers, 18,[21][22][23] graft copolymers, 24,25 and interpenetrating polymer networks 26,27 and via functionalization with ethylene glycol-terminated alkanethiols 7,[28][29][30][31] or silanes. 32,33 For the platforms dealing with PEG in a brushlike conformation, it was found that the most important parameter determining the protein resistance is the ethylene glycol monomer density on the surface n EG expressed as EG units/surface unit.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the most common bulk techniques are: making the surface more hydrophilic through a variety of processes such as plasma etching [6,[20][21][22][23]; or modifying the surface with a hydrophilic polymer such as polyethylene glycol [24][25][26][27][28][29][30]. Other methodologies have used smallscale modifications at the micro-and nanolevels to create patterned surfaces that can regulate protein and cellular behaviour [31][32][33][34][35][36].…”
Section: (B) Engineering Surfaces To Control Protein Adsorptionmentioning
confidence: 99%